The Effects Of Soft Drinks On Etched And Bonded Enamel - Banu Dinçer; Serpil Hazar; Hakan Şen (Turkish Journal of Orthodontics, 1998)

(untitled)
The purpose of this study was to investigate the effect of soft drinks on etched and bonded enamel surfaces in the patients using fixed orthodontic appliances. Soft drinks including Coca-Cola, Fanta, Regulator Water, Natural Mineral Water were used. Teeth were first divided into 2 main groups: While the enamel of the teeth in first group was etched only, the specimens in the second group received bonding application following the etching procedure. Each main group was then divided into 4 sub-groups. A cycling apparatus was designed in order to imitate oral conditions. The specimens were inserted into either of the soft drinks for 15 min. following an insertion into the artificial saliva for 2 h. This procedure was applied for 5 days for each solution. Because of establishing the control groups the same procedure was applied. But this group of teeth were inserted only into the artificial saliva for 5 days. Then, the teeth were cleaned off the wax, washed and prepared for SEM. During SEM observation, the drink-exposed surfaces were compared with their own control surfaces. It was observed under SEM that Coca-Cola and Fanta showed similar effects on enamel. Demineralized areas were observed particularly on etched group of teeth. There was a remarkable groove between experimental area which was covered with wax and areas which were inserted into Coca-cola, Fanta and Regulator water . Bonding material was found to be dissolved in Coca-cola and Fanta groups. However, same areas of teeth inserted into Soda water showed less remarkable groove. The results of this study reveal that asidic soft drinks cause demineralization on etched and /or bonded teeth Therefore it is proposed that subjects on fixed orthodontic treatment should not be allowed to drink Coca-cola and similar soft drinks.